Outsourcing in East Asia and its impact on the Japanese and Korean Labour Markets - Ahn, Sanghoon (OECD Trade Policy Papers, 2008)
This study describes the changing patterns of intermediate goods trade and foreign direct investment (FDI) in East Asia and investigates the impacts of international outsourcing on the Japanese and the Korean labour markets. The main findings of the paper are as follows. First, intra-regional trade in East Asia grew remarkably during the period 1990-2003. While overall trade with the rest of the world roughly doubled in this period, intra-regional trade in East Asia more than tripled. Second, the main factor behind increased intra-regional trade in East Asia was the trade in intermediate goods through outsourcing and the international fragmentation of production. Third, reflecting the fact that outsourcing to Asia (particularly to China) has a negative impact on the demand for workers with lower education and a positive impact on the demand for workers with higher education, relative wage shares of workers by educational attainment have changed substantially both in Japan and Korea. Fourth, our empirical analysis provides evidence of labour demand shift towards skilled labour in Japanese manufacturing as a result of outsourcing. For Korea, although the overall effects of outsourcing have been insignificant in Korea partly because a substantial part of Korean outsourcing remained directed towards Japan, our results imply that labour demand would shift away from less-skilled workers towards more-skilled workers if outsourcing to China increased and outsourcing to Japan decreased in the future